Gender gaps in reading increase during unplanned and planned school closures - Emil Smith; Ea H. Blaabæk; David Reimer; Mads M. Jæger (Proceedings of the National Academy of Sciences, 2026)
Why do girls outperform boys in education? One contributing factor might be that girls read more than boys, which fosters competencies relevant in education. Moreover, boys might rely more heavily on schools to support and encourage reading, meaning that unplanned and planned school closures disproportionally affect boys. We map the gender gap in reading in the period 2020 to 2022 using two large-scale datasets from Denmark, one measuring students’ weekly reading in school via a popular reading app and the other measuring students’ borrowing of library books. Our data document a clear gender gap in reading that increased during unplanned school closures due to the COVID-19 pandemic and planned closures due to vacations. Our findings underscore the role of schools in mitigating gender differences in reading.